2011
DOI: 10.1097/meg.0b013e328348c0bf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endoscopic papillary balloon dilation and endoscopic sphincterotomy on bacterial contamination of the biliary tract

Abstract: EPBD has a possibility of suppressing bacterial contamination of the biliary tract compared with EST in patients with small stones. A large, long-term follow-up, randomized, controlled trial is necessary to clarify whether this benefit of EPBD reduces late complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 29 publications
3
23
1
Order By: Relevance
“…Sugiyama and Atomi [13] reported that the major risk factors for recurrent choledocholithiasis after EST were diameter of CBD greater than 15 mm and sepia bile duct stones. In accordance with the results of our study, it has been reported that bacterial species did not differ between bile samples before EST and those at 7 days, 3 months, 1 year, and 5 years after EST [11], and in samples obtained at 6 months and 2 years after EST [9], the predominant species were E. coli, K. pneumoniae, Enterococcus spp., and Klebsiella oxytoca. A dilated bile duct may contribute toward long-term complications through bile stasis, which occurs because of the decrease in biliary tract smooth muscle function when the CBD widens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sugiyama and Atomi [13] reported that the major risk factors for recurrent choledocholithiasis after EST were diameter of CBD greater than 15 mm and sepia bile duct stones. In accordance with the results of our study, it has been reported that bacterial species did not differ between bile samples before EST and those at 7 days, 3 months, 1 year, and 5 years after EST [11], and in samples obtained at 6 months and 2 years after EST [9], the predominant species were E. coli, K. pneumoniae, Enterococcus spp., and Klebsiella oxytoca. A dilated bile duct may contribute toward long-term complications through bile stasis, which occurs because of the decrease in biliary tract smooth muscle function when the CBD widens.…”
Section: Discussionsupporting
confidence: 92%
“…It was believed that long-term complications of EST are associated closely with the destruction of normal anatomic structure of SO after EST, which may lead to weakening or loss of sphincter function, resulting in intestinal bile reflux and biliary tract bacterial infection [7][8][9]. It was believed that long-term complications of EST are associated closely with the destruction of normal anatomic structure of SO after EST, which may lead to weakening or loss of sphincter function, resulting in intestinal bile reflux and biliary tract bacterial infection [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Natsui et al . reported that EPBD has a possibility of suppressing bacterial contamination of the biliary tract compared with EST in patients with small stones . Therefore, it is desirable to choose EPBD for treatment of BDS whenever possible, especially in patients treated with immunosuppressants after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that EPBD could preserve the sphincter function and reduce the occurrence of duodenobiliary reflux and bacteria contamination, thus decreasing the biliary stone recurrence. 10,12 A retrospective study by Kojima et al 12 revealed that the recurrence rate of CBD stones was higher in 233 patients after EST than in 453 patients after EPBD (17.0% vs. 6.8%, p < 0.05), and the sphincter of Oddi function was protected in 70% patients after EPBD. A meta-analysis also showed that the stone recurrence rate was significantly reduced in EPBD as compared with that in EST.…”
Section: Recurrence Rate Of Biliary Stones After Epbd/eplbd or Estmentioning
confidence: 95%
“…Additionally, there was no significant difference in post-procedure pancreatitis, perforation, and cholangitis between EPLBD and EST. 10 The rate of pancreatitis after EPLBD generally ranged from 0% to 7%. 3,8,9 The higher pancreatitis rates seen with primary EPBD may be mitigated by the preceding minor EST with EPLBD.…”
Section: Endoscopic Papillary Large Balloon Dilation For Removal Of Lmentioning
confidence: 99%